A more equal world? An analysis of the global inequality trends in the period 2000-2020 - Arthur Zito Guerriero (University of Duisburg-Essen, Institute for Socio-Economics (ifso), 2024)
This paper analyzes the evolution of global interpersonal income inequality in the last decades. While some authors characterize the period 2000-2020 as an "age of convergence" (Milanovic, 2022), others argue that global inequality has remained constant (Chancel & Piketty, 2021) or even increased (Hickel, 2017). Nevertheless, all datasets used in the literature point to a decline in standard measures of relative inequality, meaning that the difference in narratives stems from the way these data are interpreted. This paper contributes to the interpretation of this period by showing that while global inequality did fall between 2000 and 2020, this trend was not the result of a truly global convergence process involving all countries, as it was mainly driven by high growth rates in Asia. Combining data from the World Income Inequality Database (WIID) with population forecasts from the United Nations, an upward trend in global income inequality is projected, even if the economic shocks of COVID-19 and the invasion of Ukraine are not taken into account. The present study shows that a significant share of the Chinese population has reached such high-income levels that further increases in these incomes will contribute to a rise in inequality. Moreover, a further reduction in global inequality will require faster income growth in sub-Saharan Africa and South Asia, whereas sustained high growth rates in East Asia will contribute to higher inequality.
Keywords: D30; D31; 330; global inequality; income distribution; China; convergence; projection